2010
DOI: 10.1016/j.aorn.2009.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Culture of Mutual Respect

Abstract: The Joint Commission mandates that hospitals seeking accreditation have a process to define and address disruptive behavior. Leaders at Maimonides Medical Center, Brooklyn, New York, took the initiative to create a code of mutual respect that not only requires respectful behavior, but also encourages sensitivity and awareness to the causes of frustration that often lead to inappropriate behavior. Steps to implementing the code included selecting code advocates, setting up a system for mediating disputes, track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 9 publications
1
39
0
Order By: Relevance
“…Regarding attributes, it was found that the most disruptive behavior conduct characteristics were concentrated in the categories of Violence and Psychological Incivility, which was also found in other studies (33)(34) . In analyzing the experience of clinical nurses with disruptive behavior in the United States, researchers found the occurrence of this behavior among all contexts of practice and among a wide range of health professionals.…”
Section: Discussionsupporting
confidence: 62%
“…Regarding attributes, it was found that the most disruptive behavior conduct characteristics were concentrated in the categories of Violence and Psychological Incivility, which was also found in other studies (33)(34) . In analyzing the experience of clinical nurses with disruptive behavior in the United States, researchers found the occurrence of this behavior among all contexts of practice and among a wide range of health professionals.…”
Section: Discussionsupporting
confidence: 62%
“…6 A Joint Commission review found that in 70% of the cases classified as sentinel events, communication was a root cause for the incident, not a technical or system failure. 6 Lateral violence may contribute to poor communication if a nurse is too intimidated by a co-worker to speak up as a patient advocate. For example, in the emergency department, patients are sometimes labeled as "frequent fliers" or drug seeking.…”
Section: Effect Of Lateral Violence On Patientsmentioning
confidence: 99%
“…6,12 Team-building sessions conducted by recognized leaders in the department should focus on building trust, clarifying roles, engaging staff in decision making, role-modeling positive interactions, and holding one another accountable for behavior that is inappropriate. 12 A crucial conversation is a conversation where the stakes are high for all members and opinions often vary.…”
Section: Skills Trainingmentioning
confidence: 99%
See 2 more Smart Citations